2015
DOI: 10.4236/jmmce.2015.33018
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Anodizing Parameters in Tartaric-Sulphuric Acid on Coating Thickness and Corrosion Resistance of Al 2024 T3 Alloy

Abstract: Abstract2024 T3 is one of aluminium alloys which are widely used in the aircraft structures. Anodizing of alluminium alloy in tartaric-sulphuric acid (TSA) electrolyte is developed to obtain more environmentally-friendly process and to produce anodize layer with better corrosion resistance. In this research work, the influences of anodizing parameters of Al 2024 T3 in TSA on the thickness, weight and corrosion resistance of the anodize layer are studied. Corrosion resistance test was carried out by conducting … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
10
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 10 publications
0
10
0
Order By: Relevance
“…116,117 For example, aircraft and marine applications of aluminum are common, but higher mechanical strength requirements compared to those of automotive applications necessitate the use of copper alloys, which reduce corrosion resistance. 118 Chromic acid anodizing of aluminum helps to reduce corrosion, but chromates are environmentally toxic, and this trade-off between strength, corrosion resistance, and the use of toxins must be evaluated. 118,119 Metrics, Tools, and Gaps in Practice.…”
Section: Environmental Science and Technologymentioning
confidence: 99%
See 1 more Smart Citation
“…116,117 For example, aircraft and marine applications of aluminum are common, but higher mechanical strength requirements compared to those of automotive applications necessitate the use of copper alloys, which reduce corrosion resistance. 118 Chromic acid anodizing of aluminum helps to reduce corrosion, but chromates are environmentally toxic, and this trade-off between strength, corrosion resistance, and the use of toxins must be evaluated. 118,119 Metrics, Tools, and Gaps in Practice.…”
Section: Environmental Science and Technologymentioning
confidence: 99%
“…118 Chromic acid anodizing of aluminum helps to reduce corrosion, but chromates are environmentally toxic, and this trade-off between strength, corrosion resistance, and the use of toxins must be evaluated. 118,119 Metrics, Tools, and Gaps in Practice. Metrics that can be used to assess progress on Principle 5 include the design life of the part, durability, and remanufacturability.…”
Section: Environmental Science and Technologymentioning
confidence: 99%
“…The chlorine ions migration occurred once a critical anodic potential or critical adsorbed chloride ions concentration was reached. The chloride ions migrated from the liquid drop/AOFs interface into the passive AOFs, resulted in initiation of pitting corrosion 43 . With time goes by, the ingress of chlorine ions caused the surface dissolution and the pitting corrosion showed in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The corrosion resistance test was performed by running a salt spray test for 336 hours and anodic polarization measurements using a potentiostat. The results of showed that the most important factor in determining the thickness and weight of the anodized layer is the temperature, followed by the applied voltage, the voltage-temperature interaction, the temperature and the duration of the layer [6]. This study presents a tool for simulating the crack growth in thermo-mechanically loaded equipment.…”
mentioning
confidence: 99%
“…Significantly, accompanied by a reduction in ductility. Mohammad Zaki [6] reveals the influences of anodizing parameters of Al 2024 T3 in TSA (Tartaric-Sulphuric Acid) on the thickness, the weight and corrosion resistance of the anodized layer are studied. The corrosion resistance test was performed by running a salt spray test for 336 hours and anodic polarization measurements using a potentiostat.…”
mentioning
confidence: 99%